2017
DOI: 10.1007/s00417-017-3650-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological assessment for early detection of retinal dysfunction in β-thalassemia major patients

Abstract: Full-field ERG and mfERG are more sensitive tools for detecting early retinal changes in β-thalassemia patients compared with ophthalmoscopy, VEP, FAF imaging and OCT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Accordingly, chelation therapy was excluded from among possible causes. Nonetheless, a recent study, 50 published after completion of our study, reported that some beta-thalassemic patients receiving chelating therapy, without presenting any visible defects, showed electroretinogram alterations. A potential future area of focus for further study should consider this examination as a possible tool for identifying early alterations, even in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 65%
“…Accordingly, chelation therapy was excluded from among possible causes. Nonetheless, a recent study, 50 published after completion of our study, reported that some beta-thalassemic patients receiving chelating therapy, without presenting any visible defects, showed electroretinogram alterations. A potential future area of focus for further study should consider this examination as a possible tool for identifying early alterations, even in asymptomatic patients.…”
Section: Discussionmentioning
confidence: 65%
“…There are studies showing that it may be toxic to the eye although it's side effects are less compared to Deferoxamine. In a recent study, ERG and mfERG responses were reduced in thalassemic patients regardless of the type of chelation therapy they received [17]. On the contrary Sakamoto et al suggested that iron-chelating agents was protected retinal neurons against excitoneurotoxicity via reduction of iron content and oxidative stress in the rats [18].…”
Section: Discussionmentioning
confidence: 92%
“…Electroretinogram and electrooculogram (EOG) are usually confirmatory of DFO retinopathy and appear to be more sensitive in detecting early retinal damage than fundoscopy alone [ 3 ]. A recent study suggests that ffERG and multi-focal ERG are more sensitive in early damage detection than visual evoked potential, FAF imaging and OCT scans in patients under chelation therapy [ 32 ]. For instance, there are reports of bilateral reductions in response densities at the central retina corresponding to RPE changes related to DFO toxicity [ 3 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%